Factors Affecting Oxygen Availability - Kartini Kartini (Rifa'Institute, 2023)
Introduction: Oxygen is a chemical substance needed by patients for treatment and or the healing process. To maintain the availability of oxygen so that it is always in an effective and efficient amount, always try in a safe condition. However, in practice, there are sometimes problems related to availability in the warehouse, such as vacancies. Methods: This research is descriptive qualitative research. The informants in this study were 9 people who were obtained using a purposive sampling technique. Result and Discussion: The results of this study describe that Human Resources still need to be added, there is a delay in goods from the supplier. Control is hampered and requires more time due to the increase in COVID-19 patients, and the output component, namely the availability of oxygen in the warehouse, is experiencing a shortage. Conclusion: The availability of oxygen, especially during the COVID-19 pandemic, is certainly unavoidable where the need increases, but several things can hinder the availability of oxygen, including delays in goods from suppliers. Control is hampered and requires more time due to the increase in COVID-19 patients.